Association Of Term Neonatal Fits With Serum Calcium Levels - Sania Sabir , Mahnoor Javed , Seema Kanwal , Sania Sabir , Mahnoor Javed , Seema Kanwal (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Background: The most prominent feature ofneurological dysfunction in neonatal period is theoccurrence of seizures. Determining its underlyingaetiology is critical. The objective of our study was todetermine association between low calcium levelsand neonatal seizures in cases presenting inPediatrics Department Holy Family Hospital,Rawalpindi.Methods: This case control study was conducted inDepartment Of Pediatrics Holy family HospitalRawalpindi from February 2015 to December 2015and included 48 neonates including 24 cases of fitsand 24 controls with exclusion criteria of prematurityand those born via caesarian section. Data wascollected through structured questionnaire. All thedata was entered and analyzed by SPSS version 17.Results: Our study comprised of 48 neonates withmean age of 7.7 ±8.1 days. Out of total 29 (60.4%)were male neonates while 19 (39.6%) were females.Among cases 46.2% had hypocalcemia while 53.8%had normocalcemia. Among controls 53.9% hadhypocalcemia while 46.1% had normocalcemia. TheOdd’s ratio was computed to be 0.714 withconfidence interval of 0.228 to 2.233 which showsassociation is insignificant.Conclusion: Neonatal fits at term were not foundto be associated with reduced calcium levels therebyother metabolic abnormalities like hypoglycemia,hyponatremia should be ruled out prior toassessment of serum calcium levels in term neonatalfits.Key Words: Neonatal Fits, Hypocalcemia.